Hubungan Status Gizi Dan Stress Dengan Siklus Menstruasi Pada Remaja Putri Di SMP Hang Tuah 1 Surabaya - Veronica Silalahi; Yuni Kurniawaty; Sri Winarni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to identify the relationship between nutritional status and the menstrual cycle in young women at Hang Tuah 1 Junior High School, Surabaya. Methods: This article used a correlation study with a cross-sectional approach using a proportional random sampling technique and obtained a total sample of 87 respondents. Data collection was carried out using a questionnaire and measuring the weight and height of female adolescents Results: The results showed that 38% of adolescents had normal nutritional status, 33% of adolescents had obesity nutritional status, 69% of respondents experienced moderate stress, 61% of respondents experienced menstrual cycle irregularities, and the results of the regression statistical test obtained p = 0.651. P> 0.05 then H1 is rejected which means there is no relationship between nutritional status, stress and the menstrual cycle in young women Conclusion: Normal nutritional status does not always result in abnormal menstrual cycles because menstrual abnormalities are caused by many things including activity, stress, and menstrual disorders. Keywords: menstruation, nutritional status, stress, menstrual cycle